Pengaruh Strategi Think Talk Write (TTW) terhadap Pemahaman Konsep Matematika Siswa Kelas VIII SMP Negeri 2 Lubuklinggau - Nur Fitriyana; Rani Asnurida (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This study aims to determine the effect of the Think Talk Write (TTW) strategy on the understanding of mathematical concepts of Grade VIII students of SMP Negeri 2 Lubuklinggau. The method used in this research is pure experiment. The population in this study were all eighth grade students of SMP Negeri 2 Lubuklinggau in the 2016/2017 school year, totaling 444 students. The sample is class VIII.9 as the experimental class and class VIII.7 as the control class taken randomly. Data collection was carried out using test techniques. The collected data was analyzed using t-test at a significant level α = 0.05, obtained tcount> ttable ie 3.48> 1.67. The average score of students' understanding of mathematical concepts on the final test of the experimental class was 25.23 and the control class was 17.44. In conclusion, there is a significant influence of the Think Talk Write (TTW) strategy on the understanding of mathematical concepts of Grade VIII students of SMP Negeri 2 Lubuklinggau. Keywords: Understanding of Mathematical Concepts, Think Talk Write (TTW) Strategies